Can we quantify the aquatic environmental plastic load from aquaculture?. (1st July 2022) - Tian, Yichao; Yang, Zongyao; Yu, Xueying; Jia, Zhen; Rosso, Massimiliano; Dedman, Simon; Zhu, Jingmin; Xia, Yuxiang; Zhang, Guangping; Yang, Jiaqi; Wang, Jingzhen
Highlights: The first framework for estimating plastic litter from aquaculture was developed. The framework was applied to a plastic load survey of oyster farming in the Maowei Sea. The plastic load from aquaculture approximates the plastic input of a river. This source-based approach to plastic litter evaluation is suitable for management. This framework can be extended to other aquaculture patterns. Abstract: Aquaculture provides livelihoods for hundreds of millions of people, but it also forms a significant source of plastic litter that poses a serious hazard to aquatic ecosystems. How to assess and subsequently manage plastic loads from aquaculture is a pending and pressing issue for aquaculture sustainability, and an important concern for water environment monitoring and management. In this study, we developed the first framework for estimating plastic litter from aquaculture by combining data from satellite remote sensing, drones, questionnaires, and in situ measurements. By acquiring multidimensional (human and nature) and multiscale (centimeter to basin scale) data, this framework helped us understand the aquaculture farming patterns and its spatial and temporal evolution, and thus estimate the plastic load it generates and suggest effective management approaches. Applying this framework, we assessed the marine plastic load from oyster floating raft farming in the Maowei Sea, a typical mariculture bay in China, with an increasing farming area. Approximately 3840 tons of plastic waste is expected to be discharged into the sea in the next four years (the average service life of a floating raft) without improvements in aquaculture waste management. Strengthening governance, timely plastic removal, innovative replacement, and transforming farmers' behavior patterns are recommended as the subsequent measures for plastic management. This framework can be extended to other regions and other aquaculture patterns, and is applicable to local, regional, and global aquaculture plastic litter assessments. It is a source-based method for evaluating plastic pollution that is more conducive to subsequent plastic management than traditional post-contamination environmental monitoring. In the context of the global expansion of mariculture and the global commitment to action to combat plastic pollution, this approach could play a critical role in the investigation and management of plastic waste in aquatic environments. Graphical abstract: Image, graphical abstract